Acipenser baerii Brandt 1869 - Çiçek, Erdoğan; Jawad, Laith; Eagderi, Soheil; Esmaeili, Hamid Reza; Mouludi-Saleh, Atta; Sungur, Sevil; Fricke, Ronald (Zenodo, 2023)
Acipenser baerii Brandt, 1869 Remarks. This species was reported by Mousavi-Sabet et al .(2019) from Tigris River. 34°33′0.39′′N, 045°46′20.02′′E) and from the Ghuretu Stream where it enters the reservoir (34°32′42.11′′N, 45°47′33.59′′E) (both about 1.5-3.5 km away from the cage-culture farm within the reservoir) in the Tigris-Euphrates basin, Kermanshah Province, western Iran, at the border of Iraq. Its presence and establishment success in Iraq should be confirmed by specimen. Published as part of Çiçek, Erdoğan, Jawad, Laith, Eagderi, Soheil, Esmaeili, Hamid Reza, Mouludi-Saleh, Atta, Sungur, Sevil & Fricke, Ronald, 2023, Freshwater fishes of Iraq: a revised and updated annotated checklist- 2023, pp. 1-49 in Zootaxa 5357 (1) on page 39, DOI:10.11646/zootaxa.5357.1.1, http://zenodo.org/record/10012543